The Use of Text To Speech Software To Improve Students Listening Skill at 3rd Grade SMPN 21 MAKASSAR - Syam, Andi Multa; Akib, Erwin; Asrianto Setiadi, Muhammad (FKIP Unismuh Makassar, 2020)
The objective of this research is to find out whether the use of text-to-speech software improves students listening skills.The researcher used Pre-Experimental design in the form of One Group Pre-test - Post-test design. There are two variables in this study. The first variable is a dependent variable and the second variable is an independent variable. Dependent variables are listening, meanwhile, the independent variable is Text-to-speech software. The population in this study is the students of SMPN 21 Makassar and the sample of this study is the 3rd-grade students where the class consists of 18 students. The instruments that the researcher used in this study are tests.The results of the research is The used Text to Speech Software were able to improve the students’ listening skill at the second at the 3rd GRADE SMPN 21 MAKASSAR. Based on the result of the reseaarch. The mean score of Pre-Test is 62,16 and the Post-Test mean score is 69,44. Based on the difference from the mean score students get in lestening skill show the improvement from pre-test to post-test where the increase of students increased by 12%. The improvement of students’ achievement significantly.